Personal reflection and experience of a Fulbright Scholar: teaching a mental health course in Vietnam's changing culture. Issue 6 (18th August 2017) - Cohen, Edward
Abstract: This paper documents the experience of developing and teaching a course on mental health for undergraduate social worker students during a semester in Vietnam. Social work is a profession at the early stages of development in Vietnam, requiring much curriculum development. There are over 40 universities with undergraduate social work education programs, but few of the faculty have had training or experience in practicing social work. The paper will summarize the main reasons for developing such a course given the current state of mental health need and services in a changing culture, as well as the current state of professional social work education and the newly established profession of social work. The author describes the contexts underlying the course—the status of social work and social work education in Vietnam, the context of mental health and mental illness in Vietnam, and curriculum adaptation to the cultural context. From this experience, the lessons learned about the role of cross-cultural critical thinking, cultural knowledge, and other strategies will be discussed about teaching a subject like mental health internationally.